2021
DOI: 10.3389/phrs.2021.1603976
|View full text |Cite
|
Sign up to set email alerts
|

International Evidence on the Impact of Health-Justice Partnerships: A Systematic Scoping Review

Abstract: Background: Health-justice partnerships (HJPs) are collaborations between healthcare and legal services which support patients with social welfare issues such as welfare benefits, debt, housing, education and employment. HJPs exist across the world in a variety of forms and with diverse objectives. This review synthesizes the international evidence on the impacts of HJPs.Methods: A systematic scoping review of international literature was undertaken. A wide-ranging search was conducted across academic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Despite the limitations in the evidence, there is a clear indication that advice services may contribute to positive wellbeing and mental health outcomes. This adds to evidence from previous reviews examining the association between advice and health (Adams et al, 2006;Allmark et al, 2013;Beardon et al, 2021) that supports the commissioning and delivery of advice services to improve public health, but highlights the weaknesses in the evidence base and our lack of understanding on mechanisms that drive this impact.…”
Section: The Health Impacts Of Advice Servicesmentioning
confidence: 63%
See 2 more Smart Citations
“…Despite the limitations in the evidence, there is a clear indication that advice services may contribute to positive wellbeing and mental health outcomes. This adds to evidence from previous reviews examining the association between advice and health (Adams et al, 2006;Allmark et al, 2013;Beardon et al, 2021) that supports the commissioning and delivery of advice services to improve public health, but highlights the weaknesses in the evidence base and our lack of understanding on mechanisms that drive this impact.…”
Section: The Health Impacts Of Advice Servicesmentioning
confidence: 63%
“…Beardon et al. (2021) found that Health Justice Partnerships around the world effectively address the social welfare issues that affect health. Our review complements this study by focusing on the wider range of settings and services outside of health justice partnerships in the UK context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA provides similar welfare advice to HJP, including providing advocacy to some clients, and has continued to receive funding from government and local councils post-2012. However, the search included pre-2012 studies and US based studies, where HJP is well-established ( 15 ). As only one HJP specific study, and only a total of four peer-reviewed welfare intervention studies with health economic evaluations were identified in this review, it indicates that there is a lack of economic evaluations of these services.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search strategy followed rapid review procedure ( 14 ). The period 1st January 1995 to 14th July 2022 used covers the period since HJP were first reported ( 15 ). The following academic databases were examined: PubMed, CINAHL, ASSIA, PsycINFO, Medline, Cochrane Library, Global Health and Web of Science.…”
Section: Methodsmentioning
confidence: 99%